“Rentabilidad de la producción agrícola del cultivo de arroz (Oryza sativa L.) en Los Ríos”. - Reyes Palma, Jefferson Daniel (2018)
X. SUMMARY This document was made in the Faculty of Agricultural Sciences of the Technical University of Babahoyo, belonging to the Province of Los Ríos. The geographic coordinates UTM X: 336860,29 and: 200863,12; at 8 masl. The area has a humid tropical climate, with an annual temperature of 24.70 ° C, annual precipitation of 2 348.00 mm, humidity of 76% and 804.7 hours of annual heliophany. The soil is flat topography, clay loam texture and regular drainage. For the elaboration of this document, bibliographic review of several scientific articles, indexed articles, books, magazines, internet, which were subjected to different analyzes, paraphrasing and summary about the profitability of rice cultivation was compiled. Based on the information gathered, rice, as the main consumer food product, has a decreasing profitability, due to lack of control of government agencies when selling the product, which goes hand in hand with the high cost of agricultural inputs, having an impact on profitability of the product, causing loss of time and money to medium and small farmers and for the producer to develop a crop with good quality seed, cultural practices, application of nutrients and phytosanitary controls according to technical references required by rice cultivation Assistance from the Ministry of Agriculture is necessary in order to obtain high yields per unit area.